PON1 and PON3 in Alzheimer's Disease: Similar Functions but Different Roles - Alessandro Trentini; Valentina Rosta; Raffaella Riccetti; Gianmarco Mola; Riccardo Galletti; Marco Pinotti; Vincenza Senia; Giovanni Zuliani; Carlo Cervellati (MDPI AG, 2024)
Paraoxonase 1 (PON1) and Paraoxonase 3 (PON3) are enzymes located on the surface of high-density lipoprotein (HDL) and share similar antioxidant properties, possibly modulated by other proteins such as Myeloperoxidase (MPO), which drives the shift from functional to dysfunctional HDL. PON1 has been extensively studied in relation to Alzheimer's Disease (AD), but the role of PON3 remains unknown. To fill this knowledge gap, the study analyzed PON3 protein levels and PON1-arylesterase activity in 99 AD patients, 100 patients with mild cognitive impairment (MCI), and 79 cognitively normal controls. The results showed that serum PON3 levels remained unchanged across all groups. In contrast, serum arylesterase activity was significantly reduced in both AD and MCI patients compared to controls (p < 0.001 for both comparisons). Surprisingly, there was no correlation between arylesterase activity and MPO protein concentration or activity. However, PON3 was found to have a significant positive correlation with both MPO concentration (r = 0.507, p < 0.0001) and MPO activity (r = 0.264, p < 0.01). In conclusion, we demonstrated for the first time that PON1 and PON3 have distinct relationships with AD, with only PON1 showing a decrease in activity in this disease, while PON3 levels remained unchanged. Another noteworthy finding was the selective correlation between PON3 and MPO, which may suggest a preferential physical association of PON3 with dysfunctional HDL.